An illustrative case of Léri-Weill dyschondrosteosis - Renata de Lima (Genetics and Molecular Biology, 2008)
We report on a girl presenting Léri-Weill dyschondrosteosis (LWD) due to deletion of the SHOX gene. Her family included individuals with short stature alone or with both short stature and mesomelia or Madelung's deformity. The deletion was demonstrated through detection of hemizygosity for microsatellite markers SHOX-CA repeat, DXYS10092, DXYS10093 and DXYS10091 localized around the SHOX gene, with retention of paternal alleles in the proband and three of her sisters who had short stature as the only clinical feature. Hemizygosity for these loci was also observed in their mother, who had short stature too. The deletion in the proband was however larger, including locus DXY10083. The proband's only sister with normal height did not carry the deletion. Family history suggests transmission of the deletion from the proband's maternal great-grandfather to her grandfather via the Y chromosome, and from the grandfather to the proband's mother via the X chromosome after crossing-over in the pseudoautosomal region proximal to the SHOX gene.